Role of CNPase in the oligodendrocytic extracellular 2′, 3′‐cAMP‐adenosine pathway. Issue 10 (6th August 2013) - Verrier, Jonathan D.; Jackson, Travis C.; Gillespie, Delbert G.; Janesko‐Feldman, Keri; Bansal, Rashmi; Goebbels, Sandra; Nave, Klaus‐Armin; Kochanek, Patrick M.; Jackson, Edwin K.
Abstract : Extracellular adenosine 3′, 5′‐cyclic monophosphate (3′, 5′‐cAMP) is an endogenous source of localized adenosine production in many organs. Recent studies suggest that extracellular 2′, 3′‐cAMP (positional isomer of 3′, 5′‐cAMP) is also a source of adenosine, particularly in the brain in vivo post‐injury. Moreover, in vitro studies show that both microglia and astrocytes can convert extracellular 2′, 3′‐cAMP to adenosine. Here, we examined the ability of primary mouse oligodendrocytes and neurons to metabolize extracellular 2′, 3′‐cAMP and their respective adenosine monophosphates (2′‐AMP and 3′‐AMP). Cells were also isolated from mice deficient in 2′, 3′‐cyclic nucleotide‐3′‐phosphodiesterase (CNPase). Oligodendrocytes metabolized 2′, 3′‐cAMP to 2′‐AMP with 10‐fold greater efficiency than did neurons (and also more than previously examined microglia and astrocytes); whereas, the production of 3′‐AMP was minimal in both oligodendrocytes and neurons. The production of 2′‐AMP from 2′, 3′‐cAMP was reduced by 65% in CNPase −/− versus CNPase +/+ oligodendrocytes. Oligodendrocytes also converted 2′‐AMP to adenosine, and this was also attenuated in CNPase −/− oligodendrocytes. Inhibition of classic 3′, 5′‐cAMP‐3′‐phosphodiesterases with 3‐isobutyl‐1‐methylxanthine did not block metabolism of 2′, 3′‐cAMP to 2′‐AMP and inhibition of classic ecto‐5′‐nucleotidase (CD73) with α, β‐methylene‐adenosine‐5′‐diphosphate did not attenuate the conversion of 2′‐AMP to adenosine. These studies demonstrate that oligodendrocytes express the extracellular 2′, 3′‐cAMP‐adenosine pathway (2′, 3′‐cAMP → 2′‐AMP → adenosine). This pathway is more robustly expressed in oligodendrocytes than in all other CNS cell types because CNPase is the predominant enzyme that metabolizes 2′, 3′‐cAMP to 2‐AMP in CNS cells. By reducing levels of 2′, 3′‐cAMP (a mitochondrial toxin) and increasing levels of adenosine (a neuroprotectant), oligodendrocytes may protect axons from injury. GLIA 2013;61:1595–1606